Assessment of anthropometric measurements of premature children with physical developmental delays at preschool age - S.N. Nasibova; A.S. Gadzhieva (Сучасна педіатрія: Україна)
Assessment of child growth and development is crucial for paediatricians, as delays in these areas have significant socio-economic implications and their treatment can be costly.